ANOMALÍA DEL CROMOSOMA 13 EN ANILLO: REPORTE DE DOS CASOS EN ELINMP - Fajardo Loo, Maria Luisa (2025)
Ring chromosome 13 is a rare structural abnormality characterized by variable loss of genetic material and clinical heterogeneity. Case presentation. We report two neonates diagnosed with this anomaly at the Instituto Nacional Materno Perinatal (INMP), Peru, who were evaluated through clinical, neurological, endocrinological, cardiological, and cytogenetic assessments using peripheral blood karyotype with GTG banding. In both cases, ring chromosome 13 with deletions at p13 and q34 was identified. The first neonate presented holoprosencephaly, panhypopituitarism, hypotonia, and micropenis, while the second showed microcephaly, periventricular leukomalacia, hearing loss, and minor dysmorphic features. Both patients exhibited motor delay and neonatal complications. Conclusion. These findings confirm the wide phenotypic variability associated with ring chromosome 13, even in the presence of similar chromosomal alterations. Early recognition of this anomaly is essential to guide treatment, provide genetic counseling, and promote a multidisciplinary approach, particularly in resource-limited settings.